Startup analyses of a megawatt heat pipe cooled reactor. (November 2022) - Ma, Yugao; Zhong, Ruicheng; Yu, Hongxing; Huang, Shanfang; Tian, Changqing; He, Xiaoqiang; Ouyang, Zeyu; Liu, Jiusong; Liu, Yu; Chai, Xiaoming
Abstract: Heat pipe cooled reactors experience temperature rises of up to 800 K during startup. The in-core heat pipes and the energy conversion system are initially frozen, which leads to a highly coupled heat transfer system that has significant safety challenges. This work modeled the system startup using a two-dimensional heat pipe model and an open-air Brayton cycle model coupled to the Heat Pipe Reactor TRANsient analysis code, HPRTRAN. The heat pipe model was validated with startup experiments showing that the predicted heat pipe wall temperature was within 30 K of the measured temperatures. The Brayton cycle model was validated against experimental data in the literature. The analysis code was then used to analyze a megawatt heat pipe reactor connected to an open-air Brayton cycle, which was used to study the influence of the external reactivity and the inherent feedback on the startup process. The simulations show that the reactor startup process is sensitive to the heat pipe operating state. The startup process can be divided into the subcritical stage, heat pipe startup stage, and increasing power stage. The power peak amplitudes are significantly reduced by slowing the angular speed of the control drum. Reducing the control drum angular speed from 0.1°/min to 0.05°/min reduced the first power peak from 2000 kW to 1000 kW. A modified reactor startup control strategy was then developed that ensures the core safety with the reactivity introduced in steps. Smaller reactivity insertions reduce the power peaks during the initial startup but lead to much longer startup times. A reasonable balance was obtained by repeated insertions of either 30 pcm or 60 pcm for safe startups of the heat pipe cooled reactor.